Digital twins enable stratification of persistent atrial fibrillation patients for ablation diminishing unnecessary heart damage - Kensuke Sakata; Carolyna A. P. Yamamoto; Adityo Prakosa; Brock M. Tice; Syed Yusuf Ali; Shane Loeffler; Eugene G. Kholmovski; Sunil Kumar Sinha; Joseph E. Marine; Hugh Calkins; David D. Spragg; Natalia A. Trayanova (npj Digital Medicine)
Abstract Pulmonary vein isolation (PVI), the standard-of-care for atrial fibrillation (AF), is effective even in some persistent AF (PsAF) patients despite atrial fibrosis proliferation, suggesting that PVI could not only be isolating triggers but diminishing arrhythmogenic substrates. Left atrial (LA) posterior wall isolation is the prevalent adjunctive strategy aiming to address PsAF arrhythmogenesis, however, its outcomes vary widely. To explore why current PsAF ablation treatments have limited success and under what circumstances each treatment is most effective, we utilized patient-specific heart digital twins of PsAF patients incorporating fibrosis distributions to virtually implement versions of PVI (individual ostial to wide antral) and posterior wall isolation. In most digital-twins (60%) PVI greatly decreased LA substrate arrhythmogenicity without the need of wider lesions or posterior wall isolation. Using digital-twin findings, a strategy was developed to stratify PsAF patients to an appropriate ablation option based on fibrosis features, thus potentially avoiding unnecessary heart damage.